Evaluation of the performance of highly modified asphalt binder using accelerated pavement testing. Issue 13 (10th November 2021) - Kwon, O.; Choubane, B.; Green, J.; Sholar, G.
ABSTRACT: A full-scale experiment was conducted at the Florida Department of Transportation (FDOT)'s accelerated pavement testing (APT) facility to evaluate the performance of a newly formulated asphalt binder commonly referred to as Highly Modified Asphalt (HiMA) binder. Test sections were constructed using three dense-graded Superpave asphalt mixtures consisting of the same aggregate components and gradation. One mixture included a polymer-modified asphalt (PMA) binder meeting PG 76-22 requirements, another contained HiMA binder at the same effective binder content, and the third one also used HiMA binder but at an additional 0.5% binder content. The subsequent accelerated testing showed that, under similarly controlled conditions, test sections using HiMA binder exhibited better rutting and fatigue cracking performance than those with PG 76-22 PMA binder. The 0.5% additional HiMA binder content resulted in negligible improved performance compared to the sections using HiMA binder at the design content. Furthermore, supplementary laboratory tests including Dynamic Shear Rheometer (DSR), Multiple Stress Creep Recovery (MSCR), softening point, and Indirect Tensile strength confirmed the improved properties of the HiMA binder and HiMA mixtures.